Space use by animals on the urban fringe: interactive effects of sex and personality. (26th November 2019) - Wat, Katie K Y; Herath, Anushika P H M; Rus, Adrian I; Banks, Peter B; Mcarthur, Clare
Abstract: Personality traits shape individual perceptions of risks and rewards, and so, should affect how animals value and use their environment. Evidence is emerging that personality affects foraging, space use, and exploitation of novel environments such as urban habitat. But the influence of personality is also hypothesized to be sex-dependent when primary motivation for space use differs between sexes, as often occurs in polygynous species. We tested the influence of personality traits, interacting with sex, on space use by the polygynous common brushtail possum, Trichosurus vulpecula, in an urban-woodland boundary in Sydney, Australia. We quantified personality traits, including exploration, using behavioral assays in an artificial arena. We also GPS-tracked free-ranging individuals, and measured range size, core area: home range, and proportional urban range. We found that personality traits affected space use either as a main effect or, as predicted, an interaction with sex. More exploratory animals, regardless of sex, had higher core area: home range ratios and proportionally larger ranges within urban habitat. However, less exploratory females yet more exploratory males had larger ranges. Our findings provide new insight into movement ecology by demonstrating, for the first time, the sex-dependent influence of personality. The demonstrated influence of personality on urban use by possums also suggests a personality filter for wildlife, as populations transition into urban areas. Finally, as individuals at the interface between urban and natural habitat are also a conduit between the two, a corollary of our findings is that there may be personality-mediated spread of disease across this boundary. Abstract : Animal personality traits, such as exploration, quantify consistent behavioral differences among individuals. These traits can influence space use and urban exploitation by individuals, but effects may also differ between the sexes. We found that more exploratory possums on the urban fringe favored urban over woodland habitat. In addition, less exploratory females but more exploratory males had larger ranges; a pattern likely driven by different primary motivators such as food (females) or access to mates (males).